2005
DOI: 10.1002/art.21595
|View full text |Cite
|
Sign up to set email alerts
|

Activity limitation in rheumatoid arthritis correlates with reduced grip force regardless of sex: The Swedish TIRA project

Abstract: Objective. To evaluate activity limitations 3 years after diagnosis of early rheumatoid arthritis (RA) in relation to grip force and sex. Methods. A total of 217 patients, 153 women and 64 men, with recent-onset RA were included. Activity limitations were reported using the Health Assessment Questionnaire (HAQ) and the Evaluation of Daily Activities Questionnaire (EDAQ). The relationships between activity limitations versus grip force (measured by the Grippit), walking speed, functional impairment, grip abilit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
33
0
6

Year Published

2007
2007
2021
2021

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 59 publications
(47 citation statements)
references
References 35 publications
6
33
0
6
Order By: Relevance
“…Additionally, three studies reported a significant correlation between grip strength and arm circumference and arm strength [15,28,30] and two studies reported a significant correlation between grip strength and jumping strength [9,16]. Also, several studies reported a significant association between grip strength and physical fitness or health status [1,7,22,36,40]. Based on present literature in the clinical setting, grip strength might serve as a general indicator for general muscle strength; however, the prediction of total muscle strength from grip strength might result in some inaccuracies on the individual level.…”
Section: Discussionmentioning
confidence: 96%
“…Additionally, three studies reported a significant correlation between grip strength and arm circumference and arm strength [15,28,30] and two studies reported a significant correlation between grip strength and jumping strength [9,16]. Also, several studies reported a significant association between grip strength and physical fitness or health status [1,7,22,36,40]. Based on present literature in the clinical setting, grip strength might serve as a general indicator for general muscle strength; however, the prediction of total muscle strength from grip strength might result in some inaccuracies on the individual level.…”
Section: Discussionmentioning
confidence: 96%
“…udo wod nio no zwią -zek po mię dzy si łą chwy tu a ogra ni cze niem ak tyw ności rucho wej cho rych na RZS [15]. W związ ku z tym mo żna za ło żyć, że zwięk sze nie si ły uchwy tu mo że pro wa dzić do po pra wy ja ko ści ży cia i spraw no ści wy ko ny wa nia czyn no ści dnia co dzien ne go.…”
Section: Discussionunclassified
“…Thyberg et al demonstrated a correlation between grip force and limitation of activity in patients with RA [15]. Therefore, hand strength improvement measured by grip force might result in improved quality of life and ability to cope with daily activities.…”
Section: Discussionmentioning
confidence: 99%
“…The Swedish TIRA project This study was conducted in association with the Swedish multi-centre early intervention project TIRA [1,3,5,16,18,33]. In total, 320 patients with recent-onset (≤1 year) RA who fulfilled ≥4 of 7 RA classification criteria or at least morning stiffness ≥60 min, symmetrical arthritis and arthritis of small joints were included in the TIRA cohort during 1996-1998.…”
Section: Methodsmentioning
confidence: 99%